The socio-philosophical significance of the culture of reading in the development of public consciousness and spirituality of youth - Ramzaevich, Ashrapov Ravil (Goodwood Publishing, 2025)
Purpose: This study aims to explore the socio-philosophical significance of reading culture in shaping the spirituality and public consciousness of youth. It emphasizes how reading contributes to the development of moral values, critical thinking, and social cohesion in the face of digital influences. Methodology/approach: The study employs qualitative philosophical inquiry supported by historical-philosophical analysis, content analysis, and comparative cultural methods. The arguments are substantiated through literature review and theoretical contributions from classical and contemporary scholars Results/findings: The findings indicate that reading culture plays a strategic role in instilling qualities such as kindness, compassion, honesty, and intellectual maturity among young individuals. It strengthens social values, encourages moral autonomy, and counters the negative impacts of digital media on spiritual growth. Reading culture emerges as a fundamental catalyst for cultural continuity and social progress. Conclusions: Reading culture not only enhances individual consciousness but also fosters spiritual resilience and ethical awareness, which are essential in maintaining generational value systems and national identity. It functions as a bridge between tradition and modernity in the moral development of youth Limitations: The study is primarily theoretical and philosophical in nature, lacking empirical validation through quantitative or longitudinal data on youth behavior and reading habits. Contribution: This research enriches the discourse on social philosophy by positioning reading culture as a dynamic subsystem within societal development. It advocates for policy and educational reforms that reinforce reading as a tool for spiritual and moral formation.